ORIGIN AND DYNAMICS OF TOURIST FLOWS IN THE REGION LOCATED IN THE LOWER DNIESTER RIVER BASIN - Ivan MOROZ (Economica)
The article analyzes the origin and evolution of tourist flows in the Lower Nistru River Basin region. In the 1980s, this area was a popular tourist destination in the former USSR, but after 1990, the number of tourists dropped drastically due to economic problems and armed conflicts. After 2000, the region began to recover, and in the period 2014-2023, the number of tourists increa- sed, reaching approximately 305 thousand visitors in 2023, most of whom were accommodated in hotels. Although the number of museum visits has fluctuated, interest in domestic tourism has increased, especially after the pandemic and the crisis in Ukraine. The region attracts tourists from Romania, Germany, Russia and Ukraine, but faces infrastructure challenges, requiring investments to capitalize on its tourism potential.